N′-(3,4-Dihydroxybenzylidene)acetohydrazide - Li, Wei-Wei (International Union of Crystallography, 2009)
In the title compound, C(9)H(10)N(2)O(3), the Schiff base molecule is approximately planar, the dihedral angle between the benzene ring and the acetohydrazide group (r.m.s. deviation = 0.034 Å) being 8.81 (7)°. An intramolecular O—H⋯O hydrogen bond is observed. In the crystal, molecules are linked into a three-dimensional network by O—H⋯O, N—H⋯O and C—H⋯O hydrogen bonds.